ORGANIZATIONAL CULTURE AND JOB SATISFACTION: INSIGHTS FROM A HIGHER EDUCATION INSTITUTION IN KAZAKHSTAN - Orynbek, Gulnar (Nazarbayev University Graduate School of Education, 2025)
Organizational culture is a valuable lens for understanding higher education institutions' management practices, performance, and change strategies. However, research on organizational culture within the context of Kazakhstani higher education remains limited. This qualitative descriptive case study aimed to explore how faculty members perceive the organizational culture of their institution and how it influences their job satisfaction. Recognizing that an institution's historical background plays a critical role in shaping its organizational culture, this study examined the interplay between the university’s historical legacy and faculty experiences. A purposive sample of 26 faculty members from 13 academic departments participated in the study. Data were collected through observations, document analysis, and semi-structured interviews. The research utilized Tierney’s six-dimensional framework of organizational culture and Schein’s three-level organizational culture model, which were adapted and expanded to create a modified framework tailored to this study. The framework incorporated eight dimensions: historical background, mission, leadership, faculty participation, information flow, resource allocation, staff development, and the role of leadership. The findings reveal how historical and organizational legacies, coupled with the process of internationalization, have shaped the institution’s culture and significantly impacted faculty satisfaction. This study contributes to a deeper understanding of the cultural dynamics in Kazakhstani higher education and underscores the importance of addressing organizational culture to enhance faculty experiences and institutional effectiveness.
Keywords: organizational culture; organizational legacies; job satisfaction; faculty members; Type of access: Embargo